Biogenesis, conservation, and function of miRNA in liverworts. (11th March 2022) - Pietrykowska, Halina; Sierocka, Izabela; Zielezinski, Andrzej; Alisha, Alisha; Carrasco-Sanchez, Juan Carlo; Jarmolowski, Artur; Karlowski, Wojciech M; Szweykowska-Kulinska, Zofia
Abstract : This review highlights recent findings on the liverwort miRNA repertoire, including Marchantia polymorpha miRNA gene organization, biogenesis, and functions, and microprocessor, auxiliary, and regulatory proteins involved in miRNA biogenesis. Abstract: MicroRNAs (miRNAs) are small non-coding endogenous RNA molecules, 18–24 nucleotides long, that control multiple gene regulatory pathways via post-transcriptional gene silencing in eukaryotes. To develop a comprehensive picture of the evolutionary history of miRNA biogenesis and action in land plants, studies on bryophyte representatives are needed. Here, we review current understanding of liverwort MIR gene structure, miRNA biogenesis, and function, focusing on the simple thalloid Pellia endiviifolia and the complex thalloid Marchantia polymorpha. We review what is known about conserved and non-conserved miRNAs, their targets, and the functional implications of miRNA action in M. polymorpha and P. endiviifolia . We note that most M. polymorpha miRNAs are encoded within protein-coding genes and provide data for 23 MIR gene structures recognized as independent transcriptional units. We identify M. polymorpha genes involved in miRNA biogenesis that are homologous to those identified in higher plants, including those encoding core microprocessor components and other auxiliary and regulatory proteins that influence the stability, folding, and processing of pri-miRNAs. We analyzed miRNA biogenesis proteins and found similar domain architecture in most cases. Our data support the hypothesis that almost all miRNA biogenesis factors in higher plants are also present in liverworts, suggesting that they emerged early during land plant evolution.